The Impact of Fishermen's Income on Fulfilling Children's Educational Needs in Pulau Osi Hamlet, West Seram District, West Seram Regency - Pinoa, Wiclif Sephnath; Lasaiba, Mohammad Amin; Nadira, Nadira (Jurnal Pendidikan Geografi Unpatti, 2022)
Fulfilling the living needs of the people of Osi Island with the characteristics of its territory which is located on a small island and has a dependence on marine products. From this, this research was studied qualitatively and quantitatively. Qualitative studies explain while quantitative studies use simple linear regression analysis techniques to predict the effect of independent variables on the dependent variable with a sample size of 40 fishing families who have school-age children. The results of the study show that the independent variable (X) namely income affects the dependent variable (Y) is determined based on the significant value in the results of simple regression analysis obtained a value of 0.04 < 0.05, which means that the X variable affects the Y variable so that it can be concluded that the income of fishermen can affect the educational needs of children which can be seen also in the known t value of 3,094, > t table 2,024, so it can be concluded that the income variable (X) affects the educational needs variable (Y)